2019
DOI: 10.21467/ajgr.7.1.45-63
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar Amendment on Soil Problems and Improving Rice Production under Salinity Conditions

Abstract: Soil with poor physio-chemical and biological properties prevent plant growth. These poor characteristics may be due to soil creation processes, but also include largely inappropriate agricultural practices and/or anthropogenic pollution. During the last 4 decades, the world has lost one-third of its cropland due to pollution and erosion. Therefore, a series of operations is required to improve and recover the soil. Biochar is a new multifunctional carbon material extensively used as a modifier to improve soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Combined application of the soil amendments has the potential of improving soil nutrient availability, with concomitant reduction of nutrient leaching loss. Other studies conducted elsewhere in the world came out with almost similar findings [13,57,58]. Of particular interest to the agronomists in Malaysia is the fact that RHB applied on acid sulfate soil in combination with bio-fertilizer fortified with beneficial bacteria can increase plant nutrient uptake and subsequently enhance the grain yield production of rice as well as its quality [59,60].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Combined application of the soil amendments has the potential of improving soil nutrient availability, with concomitant reduction of nutrient leaching loss. Other studies conducted elsewhere in the world came out with almost similar findings [13,57,58]. Of particular interest to the agronomists in Malaysia is the fact that RHB applied on acid sulfate soil in combination with bio-fertilizer fortified with beneficial bacteria can increase plant nutrient uptake and subsequently enhance the grain yield production of rice as well as its quality [59,60].…”
Section: Discussionmentioning
confidence: 63%
“…The application of GML or RHB in combination with bio-fertilizer is an excellent agronomic practice to enhance nutrient availability and plant uptake. The treatments will also increase microbial activities in the soils that affect rice growth positively [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar (BC) is a new multifunctional carbon material that is widely used as an amendment for enhancing soil quality and plant productivity [11]. It is produced by the pyrolysis process in limited oxygen levels of different straw materials such as rice straw, cotton stalks, peanut hulls, grass and animal wastes, as found in [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that saline water reduces all the physiological properties of wheat [27,28], while the biochar addition reduced the negative effects of salinity in both seasons and over seasons. Thus, saline water reduces plant growth but can be mitigated to a certain extent through biochar application [29].…”
Section: Effect Of Saline Water and Biochar On Wheat Productionmentioning
confidence: 99%